Integrated Blended Research Strategy for online teaching-learning design (Research, Society and Development, 2022)
The design of a research design leads to the formulation of doubts about which methodologies can be used, especially when it comes to educational design research. The aim of the study was to present a research strategy, with a combination of qualitative research methods. To achieve the objective, development research was carried out. The Integrated Mixed Research Strategy was developed, which was tested in an online teaching-learning design theorizing study. The strategy was structured in five modules: identification of the problem and the objective of the study, survey of theoretical reference, qualitative field study through qualitative metasynthesis, association of content analysis technique and use of instructional design elaboration methodology. The developed strategy proved to be versatile, innovative and with the potential to be replicated, bringing even more security and confidence in data analysis.